The Analysis of the role of the 5r work culture at PT Indospring Tbk - Enrico Julian Ekananda; Maulidyah Amalina Rizqi; Abdurrahman Faris Indriya (Enrichment : Journal of Management, 2023)
This study aims to analyze the implementation and role of the 5S work culture on employee performance at PT Indospring Tbk. In this study, researchers used qualitative methods with a case study approach based on the researchers' objectives to determine the impact of 5S culture on employee performance at PT Indospring Tbk. Results to improve the implementation of a successful 5R work culture in improving employee performance, efforts such as providing training and outreach about 5R to employees, providing strong support and commitment from management, and providing adequate facilities and resources to support the implementation of a 5R work culture are needed.